Module 9: The Natural World, Weather. Module 10: Culture, Customs & Traditions All over the World: Upper-Intermediate - Advanced; Class Book; учебное пособие по английскому языку для студентов ТПУ - Ануфриева М. А. Марина Александровна; Смирнова О. А. Олеся Анатольевна (General English for Technical students)
Экспериментальное пилотирование модульной программы в 2006/2007 учебном году.